2016
DOI: 10.1093/jmcb/mjw014
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin signaling and function in insulin target tissues

Abstract: Obesity-linked type 2 diabetes is one of the paramount causes of morbidity and mortality worldwide, posing a major threat on human health, productivity, and quality of life. Despite great progress made towards a better understanding of the molecular basis of diabetes, the available clinical counter-measures against insulin resistance, a defect that is central to obesity-linked type 2 diabetes, remain inadequate. Adiponectin, an abundant adipocyte-secreted factor with a wide-range of biological activities, impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
224
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(248 citation statements)
references
References 113 publications
9
224
1
14
Order By: Relevance
“…8 Adiponectin exerts its biological functions by binding to its receptor to trigger the downstream signaling pathways. 9,10 Among the identified adiponectin receptors (AdipoRs), AdipoR1 and AdipoR2 have been shown to be the most physiologically important for adiponectin functions in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Adiponectin exerts its biological functions by binding to its receptor to trigger the downstream signaling pathways. 9,10 Among the identified adiponectin receptors (AdipoRs), AdipoR1 and AdipoR2 have been shown to be the most physiologically important for adiponectin functions in vivo.…”
mentioning
confidence: 99%
“…9 Physiologically, AdipoR1 and AdipoR2 have some common and different functions. Either of them can regulate glucose and lipid metabolism, inflammation, and oxidative stress in the liver.…”
mentioning
confidence: 99%
“…These findings suggest the importance of adiponectin in the regulation of body fat mass in newborn infants. A growing body of evidence suggests that adiponectin may also play a role in the development of insulin resistance [34]. Kajantie et al reported that adiponectin concentrations in fetal circulation showed a 20-fold rise between 24 week gestation [35].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin -Adiponectin (Ad) is a protein hormone produced exclusively by adipose tissues with identified beneficial effects on insulin sensitivity and lipid metabolism [39]. In addition, Ad exerts multiple vasoprotective effects via its anti-inflammatory, antioxidant, antiapoptotic, antiatherogenic, vasodilatory, and antithrombotic properties on endothelial cells, monocytes, macrophages, leukocytes, platelets, and vascular smooth muscle cells [40].…”
Section: Endothelial Dysfunction and Metaflammationmentioning
confidence: 99%